Tipologi Wilayah Jawa Bagian Tengah Berdasarkan Sektor Konstruksi - Bangun, Dhany Saputra; Setyono, Jawoto Sih (Universitas Diponegoro, Indonesia, 2020)
The construction sector plays a significant role in the Indonesian economy. The construction sector has an influence on the economy through the inputs used or generated, absorption of the materials and labor used, as well as producing and distributing the output produced in economic activities. Its contribution and growth each year shows a particularly good value in the central part of Java. This study aims to create a regional typology in Central Java based on its construction sector. The methods used are Location Quotients, shift and share and Klassen Typology. In 2018 most of the districts/cities had a typology of fast developing regions, progressive GRDP growth in the construction sector and baseless absorption of labor. In 2019,Â central part of Java had a typology of fast-growing and relatively lagging regions, progressive GDP growth of construction sector and baseless absorption of labor. Overall, the GRDP growth in the construction sector in the central part of Java has a positive impact on the economic development of districts / cities in the central part of Java, but this is not followed by absorption of labor in the construction sector.